Hereditary multiple exostosis : a study in abnormal bone growth - Solomon, Louis (Department of Medicine, 2020)
Hereditary multiple exostosis is a generalised, heritable disorder of bone, characterised by the appearance of numerous cartilagecappecl exostoses at the juxta-epiphysial regions of the endochondral skeleton. The condition was apparently known even in Hunter's day and most of its characteristic features were described before the end of the nineteenth century. Nevertheless, the evolution of these curious lesions, their unusual distribution and the associated abnormalities of growth are still incompletely defined and largely unexplained.